2020
DOI: 10.1159/000510040
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone in Patients with Spontaneous Intracerebral Hemorrhage: An Updated Meta-Analysis

Abstract: Background: Spontaneous intracerebral hemorrhage (ICH) is a frequent cerebrovascular disorder and still associated with high mortality and poor clinical outcomes. The purpose of this review was to update a 15-year-old former meta-analysis on randomized clinical trials (RCTs) addressing the question of whether ICH patients treated with dexamethasone have better outcomes than controls. Methods: The electronic databases PubMed, SCOPUS, and Cochrane as well as web platforms on current clinical trials were searched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…365 A 1998 RCT suggests that dexamethasone does not likely cause an unacceptably high rate of complications but also does not provide a benefit. 366 More recently, a Cochrane review 367 and a meta-analysis 369 demonstrated no clear benefit to patients with ICH treated with dexamethasone or glucocorticoids. Taken together, these studies suggest that there may be some risk, in addition to a lack of benefit, for corticosteroid administration in the setting of ICH.…”
Section: Medical and Neurointensive Treatment For Ichmentioning
confidence: 99%
“…365 A 1998 RCT suggests that dexamethasone does not likely cause an unacceptably high rate of complications but also does not provide a benefit. 366 More recently, a Cochrane review 367 and a meta-analysis 369 demonstrated no clear benefit to patients with ICH treated with dexamethasone or glucocorticoids. Taken together, these studies suggest that there may be some risk, in addition to a lack of benefit, for corticosteroid administration in the setting of ICH.…”
Section: Medical and Neurointensive Treatment For Ichmentioning
confidence: 99%
“…These effects may predispose patients to coronary heart disease and elevated risk profiles following surgical interventions especially in case of high doses and prolonged dexamethasone intake. Though the risk of secondary hemorrhage in cranial surgery dependent on the use of dexamethasone has not intensively been studied and clear evidence of a beneficial or negative effect of dexamethasone is still lacking, so far [33], there are reports pointing at a potential association of glucocorticoid intake and postoperative hemorrhage. In a real-world practice setting with 36 US children's hospitals, retrospective analysis of 139,715 patients that had undergone surgery for tonsillectomy revealed dexamethasone use to be associated with an absolute increased risk of revisits for bleeding [34].…”
Section: Discussionmentioning
confidence: 99%
“…While there is evidence to recommend routine use in the setting of vasogenic edema as seen with intracerebral malignancy, steroids have failed to show benefit while increasing adverse events in ischemic stroke, intracerebral hemorrhage, spinal cord injury, and SAH, and are associated with increased mortality in the setting of traumatic brain injury. [20][21][22][23][24][25] Their association with multiple adverse events including infection, hyperglycemia, gastrointestinal hemorrhage, and delirium raises concern. 26 In our cohort, 12.7% of patients were diagnosed with an infection, a rate of infection lower than that recently reported by Miller et al, though the duration of therapy was considerably longer in their study.…”
Section: Discussionmentioning
confidence: 99%